Bednar Tumour Occurring after Malignant Melanoma Excision. (1st October 2018) - Ferlosio, Amedeo; Di Prete, Monia; Rossi, Piero; Campione, Elena; Orlandi, Augusto
Abstract : We report the case of a seventy-four-year-old man with a slow-growing 2 cm mass on the back that arose near the surgical scar of previously excised melanoma, invasive to a Breslow depth of 3 mm. Preoperative clinical diagnosis was "in-transit" melanoma metastasis. After surgical excision, histopathologic examination revealed a dermal nodular proliferation of spindle cells arranged in storiform pattern, with mild pleomorphism, infiltrating around appendages and into the subcutaneous tissue. Immunohistochemical investigation documented diffuse positivity for CD34 and vimentin of spindle cells. Scattered dendritic cells, containing dark pigment in varying proportion and positive for S100, Melan-A and HMB-45, were also observed. A final diagnosis of Bednar tumour was formulated. Subsequently, the patient developed numerous metastases from the primary melanoma and died after 18 months. Bednar tumour is a rare pigmented variant of dermatofibrosarcoma protuberans of intermediate malignant potential. The presence of pigmented cells in Bednar tumour requires careful differential diagnosis with malignant or benign pigmented skin tumours. The clinical history of a Bednar tumour developing close to the scar of a previous melanoma gives the opportunity of a critical and intriguing discussion about the potential origin of pigmented cells in this rare variant of dermatofibrosarcoma protuberans.